A Contrastive study: Motion Verbs in Some Selected Short Stories in English and Arabic (Zien Journal of Social Sciences and Humanities, 2022)
Motion verbs are those verbs that express a kind of movement such go, walk, run, and hurry and so on. Ikegami (1970:87) states that "Verbs of motion are understood in this paper as those verbs which refer to changes in locus''. Besides, the meaning of the "English Motion verbs “are classified into nine classes according to their syntactic behavior”.In Arabic, Al Mu'jam Al Wasset's definition of the word 'ḥaraka' was not very far from this definition, if not the same “the displacement of something from one place to another”. In general, Arab linguists agreed on Ibn Manzour's definition that the word motion is 'anti-statism’. The Arabic definition will be taken into consideration more than the English one because the latter definition focuses on displacement and change of state as the main feature of motion verbs. Later, it will be demonstrated that some motion verbs do not necessarily involve displacement or change of state. This paper aims at identifying the similarities and differences between English and Arabic in connecting with motion verbs to find out whether the findings are language-specific or not. In order to achieve the aims of the present paper stated above, the following steps are to be followed: a theoretical background of motion verbs in English and Arabic will be introduced, analysing the data, carrying out a contrastive study to show the similarities and differences between English and Arabic in connecting motion verbs and drawing some conclusions.The English and Arabic data collected for this paper was extracted from two short stories written by modern English and Arab authors: one story in each language. The minimum length of these stories is (1578) words and the maximum length of them is (2708) words. These two short stories are as the following: - Text number 1 is “A Mother” (1993) by James Joyce - Text number 2 is “المقدس بيت في) “1957) by الطنطاوي علي.